Дослідження напівпровідників за допомогою терагерцевої спектроскопії методом «накачування–зонд» - Вакула, М. Б. (ХНУРЕ, 2021)
The principle of operation of terahertz spectroscopy for monitoring the properties of chromium-alloyed gallium arsenide (GaAs: Cr) was considered in this work. The diagram of the terahertz spectroscopy apparatus is presented and described. The scientific novelty of the work lies in the use of a new method for studying the relaxation mechanisms of charge carriers, including the determination of the parameters of defects (traps), such as the capture cross sections, concentration, and energy positions in semiconductors with different structures.